The effect of the lattice girder on the composite action of the half slab / Mohd Zalimi Ja’afar - Ja’afar, Mohd Zalimi (2000)
The works in this project is to determine shear stress of lattice girder on the composite action of the half slab by using finite element analysis. The analysis consists of determining the maximum displacement of each model, the stress and strain value of the slab. The output values from the analysis are compared with the results obtained from experimental work carried out by the others researcher. The solid structure HX8M and BRS2 are used in the finite element analysis of LUSAS software. In this analysis both the lattice girder and concrete are specify as volume. Combination from both of this material strength will give the result of displacement when the load is applied to the Half Slab.